2020
DOI: 10.1101/2020.02.03.932004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell RNAseq atlas of the pathogenic stage ofSchistosoma mansoniidentifies a key regulator of blood feeding

Abstract: Schistosomiasis is an ancient and chronic neglected tropical disease that infects over 240 million people and kills over 200,000 of the world’s poorest people every year1, 2. There are no vaccines and because there is only one drug available, the need for new therapeutics is great. The causative agents of this disease are flatworm parasites that dwell inside the host’s circulation, often for decades, where they feed on blood and lay eggs which are primarily responsible for disease pathology. As metazoans compr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…In our study, while amplicon sequencing revealed reads carrying CRISPR-Cas9-induced mutations in SULT-OR, a knock-down of SULT-OR at the mRNA level was not evident, probably because the deletions occurred in only a small fraction of the adult cells that express SULT-OR. Single-cell sequencing data from adults shows SULT-OR is a marker of parenchymal cells [10], while our confocal microscopy data suggest the Cas9-gRNA complex penetrated better into the adult tegument and intestine compared to parenchymal tissue. The same phenomenon was previously described in the liver fluke Fasciola hepatica when delivering fluorescently labelled molecules by electroporation [52,53], suggesting the flatworm intestine as the main point of entry when this delivery approach is employed.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In our study, while amplicon sequencing revealed reads carrying CRISPR-Cas9-induced mutations in SULT-OR, a knock-down of SULT-OR at the mRNA level was not evident, probably because the deletions occurred in only a small fraction of the adult cells that express SULT-OR. Single-cell sequencing data from adults shows SULT-OR is a marker of parenchymal cells [10], while our confocal microscopy data suggest the Cas9-gRNA complex penetrated better into the adult tegument and intestine compared to parenchymal tissue. The same phenomenon was previously described in the liver fluke Fasciola hepatica when delivering fluorescently labelled molecules by electroporation [52,53], suggesting the flatworm intestine as the main point of entry when this delivery approach is employed.…”
Section: Discussionmentioning
confidence: 68%
“…However, ex vivo SULT-OR RNAi experiments in adult male worms showed no evident phenotypic effects other than becoming resistant to OXA [23]. Single-cell transcriptomic analysis of two-day-old schistosomula [9], adult worms [10], and in vitro-transformed mother sporocysts (unpublished) revealed SULT-OR mRNA is a marker of parenchymal cell clusters ( Supplementary Table S3 and Supplementary Figure S2B), while its top BLASTP hit in the planarian Schmidtea mediterranea, dd_Smed_v6_9472_0, is a marker of intestinal cells [38].…”
Section: The Sult-or Gene Belongs To a Multi-copy Locus On Chromosomementioning
confidence: 99%
See 3 more Smart Citations